(untitled) (Community Based Medical Journal, 2022)
Background: Non-communicable diseases (NCDs) are increasing trend globally and account for the majority of all new cases of morbidity and mortality. Previously, its prevalence was more in developed countries, but now it is increasing in low income settings. Early diagnosis, treatment and preventive measures will reduce the mortality, morbidity, and financial burden on families and community. Objectives: The study was carried out in a tertiary care hospital to explore the incidence of common NCDs and whether there was differentiation in ages, sexes and residences among hospitalized patients. Methods: A descriptive cross sectional type of observational study was done in a tertiary care hospital, Bangabandhu Sheikh Mujib Medical College Hospital (former Faridpur Medical College Hospital), Faridpur, Bangladesh from January 2019 to July 2019 for a period of 7 months. Patients were selected randomly in different adult medicine wards, including all sexes, races, and residences. Common NCDs included were cardiovascular diseases like hypertension (HTN), ischemic heart disease (IHD) and stroke; chronic respiratory diseases like COPD and asthma; diabetes mellitus (DM) and malignancy. Result: A total of 1119 patients were hospitalized for different reasons; among them, 891 patients were diagnosed as NCDs (79.62%). In this study, male patients were more than females (63.41% vs. 36.59%), common age groups between 46 and 60 (33%) and the next age groups between 31 and 45 (26.26%); the mean age was 41.51. Younger people aged 60 years are affected more than the elderly. Rural patients were more than urban (64.54% vs. 35.46%). Common NCDs were stroke (25.58%), hypertension (18.40%), diabetes (12.0%), ischemic heart disease (9.20%), chronic respiratory diseases (6.95%), malignancy (3.36%) and other less common non-communicable diseases (24.47%). Conclusion: Globally, the world is facing a growing burden of NCDs and it is a great challenge to face this upcoming situation. Measure should be taken, that how can we reduce the incidences, morbidity and mortality of those devastating diseases by prevention of their risk factors and early treatment. CBMJ 2021 January: vol. 10 no. 02 P: 80-84